Does the prevalence of Bonamia and Marteilia diseases be reduced on flat oysters (Ostrea edulis) of Atlantic and Mediterranean origin, when they are reared together with the Japanese oyster (Crassostrea gigas) in tidal ponds? - Bodoy, Alain; Bougrier, Serge; Geairon, Philippe; Garnier, Jacqueline; Boulo, Viviane; Heurtebise, Serge (ICES-CIEM CM 1991 / K:28, 1991)
The flat oyster Ostrea edulis was originally reared in several regions of the European waters. The tidal saline ponds on the Atlantic coasts of France were highly productive before being hit by two consecutive epizooties. Parasitic diseases were described on this species, both of them leading 10 economic losses, as heavy mortalities have usually been recorded before the oysters reach the commercial size. Repeated experiments showed that the two diseases, Marteilia refringens and Bonamia ostreae are still active in this environment. Recently, some evidences were given that haemocytoblasts of Crassostrea gigas had the ability to lyze the Bonamia cells. Therefore, in an experiment of contiguous culture of the two species of oysters, the growth, mortality and prevalence of the two diseases were recorded of two populations of the fiat oyster. The prevalence of Marteilia was higher then the one of Bonamia (49.8 % against 7.4 %). The oysters originated from the area exhibited a better growth and survival then the ones coming from mediterranean waters. However, the Mediterranean origin was significantly less sensitive then the Atlantic one to Bonamia (respective prevalence of 5.6 % and 9.2 %). The rearing in different proportions with Crassostrpa gigas, in the same oyster bags, resulted in an absence of significant difference between these proportions, thus leading to the conclusion that the mixed rearing of the two species did not reduce significantly the prevalence of Bonamia parasites on the fiat oyster. The very hi level of the prevalence for Marteilia refringens after 8 months of cultivation, should be emphasized. For this disease, a significant effect of the mixed rearing was observed which may be due 10 the pond variability. These results were discussed in terms of culture management.